Gabriel Marcel, Filosofía para un tiempo de crisis, Ediciones Guadarrama, Colección Punto Omega, Madrid, 1971, 250 pp - Valderrey, Carmen (1973)
Fil: Valderrey, Carmen. Colegio Mayor Santa María de la Almudena; España